Pengaruh Daya Tarik Iklan Gojek Versi SebelumGojek Terhadap Keputusan Penggunaan Aplikasi - Ashri Lutfia; Jamiati KN (Sekolah Tinggi Agama Buddha Nalanda, 2023)
Advertising is a type of communication in the form of visual, written or oral media. Advertisements make and encourage decisions to the viewing public that aim to attract consumers. Gojek is one of the companies that utilizes the YouTube platform as a place to attract consumers, one of which is their newest advertisement, namely BeforeGojek